2019
DOI: 10.1007/s12079-019-00515-9
|View full text |Cite
|
Sign up to set email alerts
|

Bystander effectors of chondrosarcoma cells irradiated at different LET impair proliferation of chondrocytes

Abstract: While the dose-response relationship of radiation-induced bystander effect (RIBE) is controversial at low and high linear energy transfer (LET), mechanisms and effectors of cell-to-cell communication stay unclear and highly dependent of cell type. In the present study, we investigated the capacity of chondrocytes in responding to bystander factors released by chondrosarcoma cells irradiated at different doses (0.05 to 8 Gy) with X-rays and C-ions. Following a medium transfer protocol, cell survival, proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 49 publications
2
22
1
Order By: Relevance
“…Differences in RIBEs have been observed between x-ray, gamma-ray irradiation, and hadrontherapy with carbon ions. Although the RBE is 2-3 times higher for carbon ions versus x-rays, the RIBEs are similar in magnitude [86,87].…”
Section: Contribution Of Bystander Effects To Normal Tissue Tolerancementioning
confidence: 86%
See 2 more Smart Citations
“…Differences in RIBEs have been observed between x-ray, gamma-ray irradiation, and hadrontherapy with carbon ions. Although the RBE is 2-3 times higher for carbon ions versus x-rays, the RIBEs are similar in magnitude [86,87].…”
Section: Contribution Of Bystander Effects To Normal Tissue Tolerancementioning
confidence: 86%
“…A bystander effect was observed when transferring the conditioned medium of irradiated chondrosarcoma cells to chondrocytes, but the reduction in proliferation was lower with C-ions compared with x-rays at the same doses [86]. In contrast, in bystander cells, the induction of micronuclei and cell death increased with LET when conditioned medium from irradiated cells was transferred to bystander cells deficiencies in DNA repair [88].…”
Section: Contribution Of Bystander Effects To Normal Tissue Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…Lepleux et al 18 found that the radiation-induced bystander response can be transferred from chondrosarcoma cells treated with IR to non-irradiated chondrocyte cells. A great impact on chondrocyte survival was observed at low doses.…”
Section: Discussionmentioning
confidence: 99%
“…Bystander factors secreted in the conditioned medium contributed to the reduced proliferation and elevated DNA damage level at low doses (X-rays and C-ions). Bystander biological activity was absent after dilution and heat treatment of the conditioned medium, leading the authors to suggest that factors such as TNF-α and IL-6 may have contributed to this effect 18 .…”
Section: Discussionmentioning
confidence: 99%